Character-based physics learning module through generative learning model: Student conceptual understanding - Wahyuni, Bening; Zainuddin, Zainuddin; Misbah, Misbah; Murshed, Mazlena Binti (Journal of Environment and Sustainability Education, 2024)
One of the causes of students' low conceptual understanding is the lack of instructional materials with a composition that aids students in understanding concepts independently or during classroom learning. The aim of this research is to produce a character-based learning module, particularly emphasizing the virtues of honesty, valuing others' opinions, and caring, through a valid, practical, and effective generative learning model to enhance students' conceptual understanding. This study follows a research and development approach. The development design employs the ADDIE model, tested with 29 eleventh-grade science students at SMAN 6 Banjarmasin. Data collection involved validation sheets for the learning module, observations of lesson plan implementation, student response questionnaires, and learning outcome tests. The data were then analyzed qualitatively and quantitatively. The results show: (1) the developed character-based learning module with an average score of 2.9 is declared valid, (2) the module, assessed through lesson plan implementation and student response questionnaires, is considered practical, and (3) the developed character-based learning module is effective in improving students' conceptual understanding, yielding an N-gain of 0.65 categorized as moderate, with a noticeable difference in students' character achievement before and after the learning process. In conclusion, this study affirms that the character-based learning module with a generative learning model is deemed suitable for enhancing students' conceptual understanding.